Constitutive characterization of a rare-earth magnesium alloy sheet (ZEK100-O) in shear loading: Studies of anisotropy and rate sensitivity. (August 2017) - Abedini, A.; Butcher, C.; Nemcko, M.J.; Kurukuri, S.; Worswick, M.J.
Abstract: Rare-earth magnesium alloys such as ZEK100-O offer improved ductility over other conventional magnesium alloys at room temperature; however, they exhibit significant anisotropy and complex yield behaviour. In this work, a systematic investigation of anisotropy of ZEK100-O rolled sheet in shear loading was conducted at room temperature under quasi-static conditions, as the shear deformation of these alloys is not well understood. Furthermore, uniaxial tensile and compressive characterization of the material was performed to provide context for its behaviour under shear loading. It was revealed that ZEK100-O exhibits strong anisotropy in shear which is markedly different than tensile anisotropy with unique trends that suggest the activation of different deformation mechanisms. To characterize shear anisotropy in HCP materials such as ZEK100-O, the shear response of the material should be investigated in three orientations of 0° (or 90°), 45°, and 135° with respect to the rolling direction. The selection and analysis of these directions is discussed in terms of the principal stress directions and activation of different deformations mechanisms. In order to further investigate this behaviour, the microstructure of the deformed specimens was studied using Electron Backscattered Diffraction (EBSD) analysis to quantify the active twinning systems in different test orientations. Moreover, the CPB06 yield criterion with two linear transformations was calibrated with experimental data to describe the complex anisotropic behaviour of ZEK100-O. It was established that the material exhibits asymmetry not only in tension-compression regions represented by the 1st and 3rd quadrants of yield locus but also in shear regions represented by the 2nd and 4th quadrants. Finally, the strain rate sensitivity of ZEK100-O was studied in shear tests at elevated strain rates of 10 s −1 and 100 s −1, at which positive rate sensitivity was observed. Highlights: Rare-earth magnesium alloy (ZEK100-O) shows anisotropic behaviour in shear loading. Different types of twinning modes were observed in microstructure of shear samples. ZEK100-O exhibits positive rate sensitivity under shear loading condition.